Using an analytic rubric system for the evaluation of anterior ceramic crown preparation performed by preclinical dental students - Mohammed M. Al Moaleem; Hafiz A. Adawi; Nasser M. Alahmari; Mohammed E. Sayed; Nassreen H. Albar; Abdulmajeed Okshah; Abdullah A. Meshni; Thrya S. Gadah; Abdulkarim H. Alshehri; Bandar M.A. AL-Makramani (PLoS ONE, 2025)
Background This study aimed to assess the performance of preclinical dental male and female students in performing maxillary anterior all-ceramic preparations using a validated analytic rubric system. Methods An analytical rubric for the assessment of maxillary anterior ceramic preparations was used in a preclinical phase study with two evaluators. The grading was based on a 4-point scale for all steps for crown preparation, and the total score was calculated out of 40 points. Differences in rubric parameter scores between male and female students were analyzed via an independent t test. Other tests, such as the kappa test and Pearson’s correlation coefficient, were used to measure the associations among grade point average (GPA), evaluators, and gender participants, with p <  0.050 considered a cutoff point for statistical significance. Results The study revealed that students of both genders demonstrated high performance, with females scoring a mean of 37.70 ± 1.61 (SD) and males scoring a mean of 36.50 ± 2.36 (SD). A significant difference in the average overall score was recorded by both evaluators (p =  0.034). The highest value was for intact gingival margins and surrounding tissues (3.89 ± 0.31 males, 3.92 ± 0.28 females), and the lowest value was for axial wall reduction (3.50 ± 0.36 males, 3.62 ± 0.42 females). Among the different parameters, only the finish line form parameter was significantly different (p =  0.011), as found by evaluator 1. Inter-rater reliability analysis revealed varying levels of agreement between the evaluators. Strong positive correlations were found between several rubric parameters, but students’ GPA had a weak, nonsignificant correlation with their preclinical performance (p =  0.495). Conclusion The analytic rubric revealed minor gender differences in preclinical performance, with female students performing slightly better. The rubric demonstrated varying inter-rater reliability and positive correlations across parameters. However, GPA showed limited correlation with preclinical performance.